Dysregulation of the B lymphocyte compartment in patients with chronic graft-versus-host disease - Habenicht, Katharina Marie; Bootz, Anna; Schneider, Alexandra; Schäfer, Simon; Hoffmann, P.; Winkler, Julia; Wolff, D.; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Expansion of Plasmablasts at Day 90 after Allogeneic Stem Cell Transplantation Predict Chronic Gvhd - Habenicht, Katharina Marie; Bootz, Anna; Schäfer, Simon; Vasova, Ingrid; Fante, Matthias; Schneider, Andrea; Rehli, Michael; Hoffmann, Petra; Rösler, Wolf; Edinger, Matthias; Herr, Wolfgang; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Functional Fc receptors are crucial in antibody-mediated protection against cytomegalovirus - Bootz, Anna; Reuter, Nina; Nimmerjahn, Falk; Britt, William J.; Mach, Michael; Winkler, Thomas H. (European Journal of Immunology, 2024)
Human cytomegalovirus is a medically important pathogen. Previously, using murine CMV (MCMV), we provided evidence that both neutralizing and nonneutralizing antibodies can confer protection from viral infection in vivo. In this study, we report that serum derived from infected animals had a greater protective capacity in MCMV-infected RAG−/− mice than serum from animals immunized with purified virus. The protective activity of immune serum was strictly dependent on functional Fcγ receptors (FcγR). Deletion of individual FcγRs or combined deletion of FcγRI and FcγRIV had little impact on the protection afforded by serum. Adoptive transfer of CD115-positive cells from noninfected donors demonstrated that monocytes represent important cellular mediators of the protective activity provided by immune serum. Our studies suggest that Fc–FcγR interactions and monocytic cells are critical for antibody-mediated protection against MCMV infection in vivo. These findings may provide new avenues for the development of novel strategies for more effective CMV vaccines or antiviral immunotherapies.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Antibodies; Cytomegalovirus; Fc receptor; Monocytes

Protective capacity of neutralizing and non-neutralizing antibodies against glycoprotein B of cytomegalovirus - Bootz, Anna; Karbach, Astrid; Spindler, Johannes; Kropff, Barbara; Reuter, Nina; Sticht, Heinrich; Winkler, Thomas; Britt, William J.; Mach, Michael (PLoS Pathogens, 2017)
Human cytomegalovirus (HCMV) is an important, ubiquitous pathogen that causes severe clinical disease in immunocompromised individuals, such as organ transplant recipients and infants infected in utero. Antiviral chemotherapy remains problematic due to toxicity of the available compounds and the emergence of viruses resistant to available antiviral therapies. Antiviral antibodies could represent a valuable alternative strategy to limit the clinical consequences of viral disease in patients. The envelope glycoprotein B (gB) of HCMV is a major antigen for the induction of virus neutralizing antibodies. However, the role of anti-gB antibodies in the course of the infection in-vivo remains unknown. We have used a murine CMV (MCMV) model to generate and study a number of anti-gB monoclonal antibodies (mAbs) with differing virus-neutralizing capacities. The mAbs were found to bind to similar antigenic structures on MCMV gB that are represented in HCMV gB. When mAbs were used in immunodeficient RAG-/- hosts to limit an ongoing infection we observed a reduction in viral load both with mAbs having potent neutralizing capacity in-vitro as well as mAbs classified as non-neutralizing. In a therapeutic setting, neutralizing mAbs showed a greater capacity to reduce the viral burden compared to non-neutralizing antibodies. Efficacy was correlated with sustained concentration of virus neutralizing mAbs in-vivo rather than their in-vitro neutralizing capacity. Combinations of neutralizing mAbs further augmented the antiviral effect and were found to be as potent in protection as polyvalent serum from immune animals. Prophylactic administration of mAbs before infection was also protective and both neutralizing and non-neutralizing mAbs were equally effective in preventing lethal infection of immunodeficient mice. In summary, our data argue that therapeutic application of potently neutralizing mAbs against gB represent a strategy to modify the outcome of CMV infection in immunodeficient hosts. When present before infection, both neutralizing and non-neutralizing anti-gB exhibited protective capacity.
EVALuna2:33722